Optimization of silane sol–gel coatings for the protection of aluminium components of heat exchangers. (6th March 2013) - Naderi, R.; Fedel, M.; Urios, T.; Poelman, M.; Olivier, M.‐G.; Deflorian, F.
<x xml:space="preserve">Abstract</x> Despite the relatively low mechanical properties respect to the aluminium alloys but due to high thermal exchange capacity, pure aluminium (AA1XXX series) is widespread for industrial applications for heat exchanger components or cooling systems (like refrigerator systems). The corrosion protection properties of aluminium components are commonly enhanced by applying organic coatings or by performing chemical conversion treatments on aluminium surface. One of the routes for the protection of aluminium components for heat exchangers is the application of silane sol–gel coatings. In this work, a thin silane sol–gel coating improving the corrosion protection of aluminum for heat exchanger and avoiding the loss of thermal exchange due to the presence of the protective layer was developed. Prior to deposit, the silane layer as a mixture of three different silicon alkoxides precursors (such as tetraethoxysilane, glycidoxypropyltrimethoxysilane and methyltrithoxysilane), the optimum surface chemical treatment of the 1050 aluminum alloy, widely employed in the heat exchanger and cooling system industry, was investigated using electrochemical impedance spectroscopy (EIS). In order to enhance protective properties, different amounts of nano‐sized sodium montmorillonite were embedded into the silane network. Through taking advantage of some parameters extracted from EIS, the most efficient concentration of nanoclay was determined, confirmed by scanning electron microscopy and Fourier transform infrared analysis as well. The resistance of the different sol–gel layers to thermal cycles (strictly related to the application in the heat exchanger industry) was carried out to stress the sol–gel coating. The behavior of the investigated sol–gel layer after the thermal cycles was evaluated by means of EIS. Copyright © 2013 John Wiley & Sons, Ltd.